Diastereoselective Synthesis of 3,3-Disubstituted Oxindoles from N-Aryl-3-Chlorooxindoles Bearing C–N Axial Chirality via Nucleophilic Substitution - Nakazaki, Atsuo; Miyagawa, Keitaro; Nishikawa, Toshio (Synlett, 2015)
Diastereoselective synthesis of 3,3-disubstituted oxindoles was examined using racemic N-aryl-3-chlorooxindoles bearing C–N axial chirality. The reaction involved the nucleophilic substitution of 3-chlorooxindoles via an ortho-azaxylylene intermediate in the presence of AgBF4 and MS 4 Å. High diastereoselectivities (up to >95:<5) were achieved in the formation of 3-alkyl-3-aryloxindole derivatives when electron-rich arenes were used.
Keywords: 3,3-disubstituted oxindole; C–N axial chirality; ortho-azaxylylene